The Effect of Company Size, Net Profit Margin, and Debt to Equity Ratio on Income Smoothing in Indonesia’s Textile and Garment Sector - Laila, Yulia; Febrina, Reni; Rahman, Muthia; Anggi Lubis, Putri (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study aims to examine the effects of company size, net profit margin (NPM), and debt-to-equity ratio (DER) on income smoothing practices in textile and garment companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Income smoothing is a managerial action designed to reduce profit fluctuations, thereby presenting a more stable financial performance and increasing stakeholder confidence. This quantitative research employs multiple linear regression analysis, accompanied by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that partially, company size, NPM, and DER each have a significant effect on income smoothing. Simultaneously, these three variables also significantly influence income smoothing practices, with an explanatory power of 85.7%. These findings suggest that the combination of firm size, profitability, and capital structure significantly contributes to managerial decisions related to income smoothing. This research enriches empirical evidence on earnings management behaviour. It provides implications for investors, auditors, and regulators in evaluating the quality of financial reporting and corporate transparency within Indonesia’s textile and garment sector.